New approaches to e-reserve : linking, sharing and streaming - Cheung, Ophelia (Chandos information professional series., 2010)
Aimed at academic library practitioners, this book describes how e-reserve services can evolve and adapt to the changing virtual learning environment of higher education. New Approaches to E-Reserve includes detailed descriptions and extensive step-by-step illustrations to provide readers with the tools required to implement the techniques covered within.